Age estimation of a Thai population based on maturation of the medial clavicular epiphysis using computed tomography - Pattamapaspong,N. (Elsevier Ireland Ltd, 2015)
© 2014 Elsevier Ireland Ltd. Ossification of the medial clavicular epiphysis plays an essential role in age estimation for forensic analyses. This study was designed to assess clavicular development in a Thai population using thin-slice computed tomography. Ossification status of the medial clavicular epiphysis was determined in 409 patients using a 5 stage classification by Schmeling et al. Stages 2 and 3 were further subclassified into early (stage a), intermediate (stage b), and late phases (stage c) using criteria from Kellinghaus et al. The sub-stage classification increased accuracy of age estimation particularly within stage 3. Results from this study can be used as a more accurate, Thai specific reference for estimating age. For Thai legal proceedings, we recommend using stage 4 of maturation to represent age. >. 18 years and stage 5 occurring at >20 years.